Establishment of a triplex TaqMan quantitative real-time PCR assay for simultaneous detection of Cymbidium mosaic virus, Odontoglossum ringspot virus and Cymbidium ringspot virus - Sun, Aiqing; Wang, Lihua; Zhang, Yiping; Yang, Xiumei; Wei, Yi; Yang, Dong; Li, Wenhan; Wu, Xuewei (Frontiers in Microbiology, 2023)
Orchids are significant ornamental plants whose viral infection results in substantial economic damage. Cymbidium mosaic virus (CymMV), Odontoglossum ringspot virus (ORSV), and Cymbidium ringspot virus (CymRSV) represent three important and prevalent orchid viruses. The detection system proposed in this study uses a triplex TaqMan quantitative real-time PCR assay to identify CymMV, ORSV, and CymRSV in a simultaneous manner. We designed specific primers and probes for CymMV, ORSV, and CymRSV, with amplified sequences of 156 bp, 148 bp, and 145 bp, respectively. The minimum detection limit of the triplex qRT‒PCR assay for CymMV and CymRSV was 1 copy/assay, and the minimum detection limit was 10 copies/assay for ORSV. The minimum stable detection limits for CymMV, ORSV, and CymRSV were 10, 102, and 102 copies/assay, respectively. Therefore, this system exhibited higher sensitivity (approximately 10 to 104-fold) than RT‒PCR. The intra- and interassay CVs of Cq values are less than 0.55% and 0.95%, respectively, indicating that the triplex assay is highly reliable and accurate. In addition, 66 samples from five different orchid genera were analyzed using the established assay and gene chip. The detection results demonstrated that the triplex probe qRT-PCR demonstrated higher sensitivity than the gene chip, indicating that the triplex real-time PCR assay could be used for the detection of field samples. Our findings suggest that the triplex real-time RT‒PCR detection system represents a rapid, simple, and accurate tool for detecting CymMV, ORSV, and CymRSV on orchids.